Systematic review of the hospice performance literature. Issue 4 (October 2020) - He, Mengying; O'Connor, Stephen J.; Qu, Haiyan; Menachemi, Nir; Tucker, Rodney; Shewchuk, Richard M.
Abstract : Background: Hospice is the key provider of end-of-life care to patients. As the number of U.S. hospice agencies has rapidly increased, the performance has been scrutinized more deeply. Purpose: To foster understanding of how hospice performance is measured and what factors are associated with performance, we conducted a systematic review of empirical research on hospice performance in the United States. Methods: Both structure–process–outcome and structure–conduct–performance frameworks were applied to categorize and summarize the hospice performance literature. A total of 36 studies were included in the systematic review. Results: Hospice agencies adopted different strategies (e.g., service provision strategy and staffing strategy) to improve performance. Two strategic approaches (innovation and volunteer usage) were associated with better outcomes. Hospice organizational factors, market environment, and patient characteristics were related to hospice strategic conduct and performance. Majority of hospice performance studies have examined the relationship between hospice structure and strategic conduct/process, with fewer studies focusing on structure performance and even fewer concentrating on strategy performance. Practice Implications: Patient, organizational, and market factors are associated with hospice strategic conduct and performance. The majority of the literature considered the impact of hospice organizational characteristics, whereas only a few studies included patient and market factors. The summarization of factors that may influence hospice performance provides insight to different stakeholders.